Pengaruh Pelatihan Soft Skills Terhadap Mutu Pelayanan Asuhan Kehamilan Bidan Praktik Mandiri - Anis Setyowati (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2022)
Pregnancy care quality is an important indicator to determine the status of maternal and child health. Quality of current pregnancy care is lacking, this is evidenced by the increasing AKI. Upbringing said to be qualified if idikator quality are met. Quality indicators include the structure, process (hard skills and soft skills) and outcomes (patient satisfaction). Soft skills are important components namely communication and empathy. Communication skills and empathy will determine the success of a given implementation. Issues that are not resolved to make pregnant women disappointed and dissatisfied, so that the quality of care of pregnancy is said to be ugly. This study aimed to analyze the influence of soft skills training modules for the quality of pregnancy care services at midwife independent practice. The study design is experimental with pre and post intervention. Subjects were selected based on the inclusion criteria. The subject is the independent practice midwives number 9 BPM as the treatment group and 9 BPM as a control group. Determination of the treatment and control groups by simple random sampling. Data were analyzed by two sample paired t test, and test simple linear regression to assess the influence of soft skills training modules for the quality of care services in pregnancy. The results of research that there are differences in the soft skills of midwives in the treatment group before and after training (p <0.001), there was no difference soft skills possessed by a midwife in the control group before and after training (p = 0.466). There are differences in quality of midwifery services in the treatment group before and after training (p <0.001), there are no differences in the quality of midwifery services in the control group before and after training (p = 0.311). There is no significant influence of soft skills training module on the quality of pregnancy care in the treatment group and the large effect that amounted to 49.3%. Soft skills training modules influence the quality of pregnancy care services at midwife independent practice, so it's important every midwife to improve communication skills and empathy in every phase of care provided, in order to improve the health of mothers and children.